UPAYA MENINGKATKAN KEMAMPUAN MOTORIK HALUS ANAK USIA DINI DENGAN PEMBUATAN ALAT PERMAINAN EDUKATIF (APE) BERBASIS BARANG BEKAS DI TK NEGERI DHARMA WANITA MUARA BULIAN - Arum Fuji Widiastuti; Sukendro; Akhmad Fikri (lembaga Sepercenter, 2026)
This study aimed to improve the fine motor skills of children aged 5–6 years through the activity of creating Educational Play Tools (APE) from recycled materials at TK Negeri Dharma Wanita Muara Bulian. The study employed a Classroom Action Research (CAR) design conducted in two cycles, with each cycle consisting of planning, action, observation, and reflection stages. The research subjects were 15 children in Group B3, consisting of 6 boys and 9 girls. Data were collected through observation and documentation, while data analysis was carried out using descriptive quantitative methods by calculating mean scores and learning mastery percentages. The results showed that the activity of creating Educational Play Tools (APE) from recycled materials effectively improved children's fine motor skills. In the pre-action stage, the average fine motor skill score was 8.26. After the implementation of Cycle I, the average score increased to 13.20. Furthermore, in Cycle II, a significant improvement was observed, with the average score reaching 29.93 and the classical mastery percentage achieving 93%. The improvement was reflected in the children's abilities to cut, paste, arrange, and assemble recycled materials into educational play tools. Based on the findings, it can be concluded that the activity of creating Educational Play Tools (APE) from recycled materials is effective in improving the fine motor skills of children aged 5–6 years at TK Negeri Dharma Wanita Muara Bulian.